2021
DOI: 10.32725/kont.2021.018
|View full text |Cite
|
Sign up to set email alerts
|

Mother-infant bonding and its associated factors during postpartum period

Abstract: The aim of the study was to determine the relationship between the selected factors (age, education, parity, child planning, skin-toskin contact (SSC) support, breastfeeding, partner support satisfaction, a child with an illness, risk of depression) and their influence on postpartum mother-infant bonding (MIB) in Slovak women. Methods: A cross-sectional study was used. To collect the relevant data, the Postpartum Bonding Questionnaire (PBQ) and Edinburgh Postnatal Depression Scale (EPDS) were used. The questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
(32 reference statements)
1
10
1
Order By: Relevance
“…Also, it should be noted that bonding was measured up to 12 months of the infant's age (with a mean at 6 months). However, the PBQ was designed for use in the early postpartum period (40,61), and it has been mostly used and validated within the first 3 months after childbirth (87)(88)(89)(90). Nevertheless, some other studies applied the PBQ within the first postpartum year [e.g., (91,92)].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it should be noted that bonding was measured up to 12 months of the infant's age (with a mean at 6 months). However, the PBQ was designed for use in the early postpartum period (40,61), and it has been mostly used and validated within the first 3 months after childbirth (87)(88)(89)(90). Nevertheless, some other studies applied the PBQ within the first postpartum year [e.g., (91,92)].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal–infant bonding is a maternal-driven process of a passionate tie between a mother and her baby ( 1 , 2 ). Shreds of evidence showed that this passionate bond begins during the prenatal period and remains all over the child's life ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to popular belief, men are now more involved in housework and, in particular, in monitoring the progression of their children (Nomaguchi and Milkie, 2020;Bueno and Vieira, 2014). Furthermore, more recent studies show that the husband's presence, assistance, and support throughout the gestational period are essential elements that might impact the development of the maternal role and, as a result, positively interfere with mother-infant bonding (Cremonese et al, 2017;Mazúchová et al, 2021). In addition, several studies show that women who report feeling supported by their spouse have fewer symptoms of depression, anxiety, and stress (Lebel et al, 2020;Stapleton et al, 2012).…”
Section: Discussionmentioning
confidence: 99%